Forestry in Ireland - Bailey, William F. (Statistical and Social Inquiry Society of Ireland, 1889)
In view of the proposed extension of the Land Purchase Acts, the question of the protection and development of Forestry in Ireland is one of very great importance and interest to the entire community. The effect of transferring to the occupiers the ownership of their holdings has in this respect been up to the present overlooked. Those who have opportunities of travelling much through Ireland, must very quickly notice the result of such sales of farms as regards the plantations thereon. It is pitiable in many cases to see the occupier, as soon as he gets a conveyance executed to himself, proceed to cut down and sell any trees that may be on his holding. In some instances these trees were planted for ornament, in others to give shelter; but in most cases they have been placed on parts of the farm which otherwise would be waste and useless.
Read Tuesday, 2nd July, 1889
Keywords: Forestry; Land use; 314.15